2013
DOI: 10.1556/oh.2013.29535
|View full text |Cite
|
Sign up to set email alerts
|

The use of Integra dermal regeneration matrix in the surgical treatment of a recurrent, extensive malignant skin lesion in the temporal region

Abstract: Authors report on the use of Integra dermal regeneration template after excision of an extended, recurrent skin tumor in the temporal region. The area covered with Integra was 180 cm2. Skin grafting to cover Integra was performed on the 28th day. Both Integra and the skin transplant were taken 100%. Integra dermal regeneration template can provide good functional and aesthetic result in the surgical management of extended skin tumors over the skull.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Integra®, a bi-layered dermal regeneration matrix, has demonstrated considerable success in various reconstructive applications, including complex wounds and soft tissue defects, as well as in cancer resection [14][15][16]. It acts as a scaffold for cellular infiltration, angiogenesis, and the formation of new tissue, ultimately integrating with the surrounding tissue and promoting wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Integra®, a bi-layered dermal regeneration matrix, has demonstrated considerable success in various reconstructive applications, including complex wounds and soft tissue defects, as well as in cancer resection [14][15][16]. It acts as a scaffold for cellular infiltration, angiogenesis, and the formation of new tissue, ultimately integrating with the surrounding tissue and promoting wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the first review of the literature about studies that describe dermal substitutes’ utilisation in reconstruction after skin tumour excision. Table enlists publications available until July 2017 …”
Section: Discussionmentioning
confidence: 99%
“…NMSC present quite high recurrences' rates, and we evaluated their incidence in the studies reviewed. Of them, 25 did not report data about recurrence or did not provide the complete text in English in order to evaluate this aspect . Eleven studies showed no recurrences among their patients, while 6 articles reported cases of recurrence that ranged from 5% to 25% …”
Section: Discussionmentioning
confidence: 99%